Relevance of Islamic Political Thought According to Al-Mawardi in Indonesia - Bayu Karunia Putra; Azizatul Farhaini; Dinatul Aini; Siti Nurjannah; Noviana Noviana; Iza Martha Padila; Nanik Azizah; Husnul Maab (Peneliti.net, 2023)
This article aims to analyze the relevance of Islamic political thought according to Al-Mawardi in Indonesia. Topic is important and interesting, because Al-Mawardi is one of the figures who are experts in the field of fiqh, especially those directly related to fiqh siyasi and is a figure who has a very large influence on Islamic political thought. Research method used is the literature review method, in which sources and data are obtained from the Goggle Scholar, SINTA, and Publish or Perish databases. In this method, researcher uses a descriptive qualitative approach, in which this method utilizes qualitative data and is described descriptively. Data collection technique uses literature review techniques carried out by researchers to collect valid, complete, and relevant information related to the topic of the problem which is the object of research. Data analysis technique used a literature review analysis technique, in which this research was conducted by reading literary sources to obtain the necessary data. The author finds that, connection with